Treatment fidelity in the Tinnitus Retraining Therapy Trial - Scherer, Roberta W. (Trials, 2020)
BACKGROUND: Treatment fidelity, defined as ensuring that the recipient receives the intended intervention, is a critical component for accurate estimation of treatment efficacy. Ensuring fidelity and protocol adherence in behavioral trials requires careful planning during the design phase and implementation during the trial. The Tinnitus Retraining Therapy Trial (TRTT) randomized individuals with severe tinnitus to tinnitus retraining therapy (TRT, comprised of tinnitus-specific educational counseling (TC) and sound therapy (ST) using conventional sound generators (SGs)); Partial TRT (TC and placebo SGs); or standard of care (SOC), using a patient-centered care approach. Study audiologists administered both types of counseling in the TRTT, creating a challenge for managing protocol adherence. METHODS: We developed methods to enhance treatment fidelity including training, competency assessment, scripts, visual aids, and fidelity monitoring. Protocol monitors identified critical topics and content to be addressed for each type of counseling session, prepared corresponding scripts, and developed training aids and treatment-specific checklists covering those topics. Study audiologists’ competency assessment required submission and review by the protocol monitors of an audiotape of one TC and one SOC counseling session. Treatment-specific aids included scripts, a 3-D model of the ear, handouts, and for TC, an illustrated flip-chart with talking points that followed the scripted content. During the trial, audiologists completed treatment-specific checklists during each counseling session, indicating topics covered/discussed and submitted audiotapes of counseling sessions. Protocol monitors reviewed audiotapes using corresponding treatment-specific checklists. Results for individual checklist items were tabulated and proportions calculated. RESULTS: Twenty-five audiologists were certified for TC and/or SOC counseling and 24 completed at least one counseling session. Adherence to each of 33 critical items on the TC checklist as assessed by the protocol monitor ranged from 70 to 100% across 37 counseling sessions (median 97%), with no difference between adherence for TRT (median, 97%) and partial TRT (median, 100%). Adherence to each of 44 critical items on the SOC checklist across 30 SOC counseling sessions ranged from 42 to 100% (median, 87.5%). CONCLUSION: The TRTT used multiple methods to address treatment fidelity. The close adherence to each treatment type was critical for evaluating the efficacy of the study interventions in this randomized trial. TRIAL REGISTRATION: clinicaltrials.gov NCT01177137. Registered on 5 August 2010.